Attenuation of foot pressure during running on four different surfaces: asphalt, concrete, rubber, and natural grass - Tessutti, V.; Ribeiro, A. P.; Trombini-Souza, F.; Sacco, I. C. N. (Journal of Sports Sciences, 2012)
The practice of running has consistently increased worldwide, and with it, related lower limb injuries. The type of running surface has been associated with running injury etiology, in addition other factors, such as the relationship between the amount and intensity of training. There is still controversy in the literature regarding the biomechanical effects of different types of running surfaces on foot-floor interaction. The aim of this study was to investigate the influence of running on asphalt, concrete, natural grass, and rubber on in-shoe pressure patterns in adult recreational runners. Forty-seven adult recreational runners ran twice for 40 m on all four different surfaces at 12 ± 5% km · h-1. Peak pressure, pressure-time integral, and contact time were recorded by Pedar X insoles. Asphalt and concrete were similar for all plantar variables and pressure zones. Running on grass produced peak pressures 9.3% to 16.6% lower (P < 0.001) than the other surfaces in the rearfoot and 4.7% to 12.3% (P < 0.05) lower in the forefoot. The contact time on rubber was greater than on concrete for the rearfoot and midfoot. The behaviour of rubber was similar to that obtained for the rigid surfaces - concrete and asphalt - possibly because of its time of usage (five years). Running on natural grass attenuates in-shoe plantar pressures in recreational runners. If a runner controls the amount and intensity of practice, running on grass may reduce the total stress on the musculoskeletal system compared with the total musculoskeletal stress when running on more rigid surfaces, such as asphalt and concrete.